The Concept of Musyarakah in Surah Al Kahfi verse 79 - Arif Luqman Hakim; Ahmad Syifa'ul Abror (Iqtishodia: Jurnal Ekonomi Syariah, 2023)
In social muamalah, especially in terms of transactions, there are contracts included in it, including sale and purchase contracts and capital. the concept of capital contracts in Islam is known to be two things, namely mudharabah and musyarakah. In the context of the dynamics of today's society, it is musyarakah that is often used rather than mudharabah in the scope of business and property ownership. In the Qur'an itself, there are three verses that explain about musyarakah, including; the 12th verse in Surah an-Nisa', the 38th verse in Surah ash-Shad, and the 79th verse in Surah al-Kahf. This research tries to discuss more deeply the concept of musyarakah contained in Surah Al-Kahf verse 79 and compares it with the hadiths and opinions of the madzhab imams. This research uses the method of literature (library research). Then the conclusion is obtained, namely that the 79th verse in Surah al-Kahf explains the concept of musyarakah, namely there is the concept of ownership of property owned by several people using the Shirkah Amlak Jabar/Ijbari contract. The contract is a joint ownership contract, whether the contract is consented to or not. In this case, it is joint ownership that occurs from the cause of inheritance.